2009
DOI: 10.1080/09511920802546814
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of cam-follower motion using B-splines

Abstract: This paper proposes design of cam-follower velocity curve by using B-spline polynomials. B-spline polynomials are smooth curves defined by control points. Curve shape can be modified by changing the control points. The traditional design method for improving the motion characteristics of the follower is to find an optimum displacement curve for which follower velocity, acceleration curves to be continuous and their peak values as small as possible (i.e. minimum jerk). B-spline polynomials of degree three and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Mandal and Naskar (2009) discuss the effect of introducing a control point in a B-spline synthesis of the cam motion program and verify their theoretical prediction experimentally (Naskar and Mandal, 2012). Sateesh et al (2009) focus on the design of velocity function represented by a 3rd degree B-spline polynomial with six control points. Flocker (2012) presents a modified trapezoidal acceleration profile whose magnitude can be adjusted freely based on designer's choice.…”
Section: Introductionmentioning
confidence: 93%
“…Mandal and Naskar (2009) discuss the effect of introducing a control point in a B-spline synthesis of the cam motion program and verify their theoretical prediction experimentally (Naskar and Mandal, 2012). Sateesh et al (2009) focus on the design of velocity function represented by a 3rd degree B-spline polynomial with six control points. Flocker (2012) presents a modified trapezoidal acceleration profile whose magnitude can be adjusted freely based on designer's choice.…”
Section: Introductionmentioning
confidence: 93%
“…1. Objective functions By substituting the values of the above parameters into equation (32), we have:…”
Section: Optimization Model and Solutionmentioning
confidence: 99%
“…However, the high-speed ones do exhibit relatively complex dynamic behavior, which obviously deviates from the assumed motions at low speed. 6 It was reported that 25 the modified trapezoidal cam profile with an adjustable forward and backward acceleration was suitable for multiple-dwell cam and follower applications. Based on the actual situation, a modified trapezoidal curve in a normalized form is adopted to represent the follower acceleration profile in this paper.…”
Section: Formulation Of Optimizationmentioning
confidence: 99%
“…Traditional methods used in cam design have provided a number of ways to express a cam profile mathematically, including cycloidal curve, modified sine curve, modified trapezoidal curve, and polynomial curve. [4][5][6] These curves not only satisfied the actual needs over a wide range of speeds but also were defined as a relatively concise expression. A universal Hermite cam displacement was suggested to minimize and restrict vibrations in high-speed cam-follower systems over a range of speeds by Jiang et al, 7 and as a result the designers could arbitrarily select the residual vibration or contact stress as quantifiable cam properties in optimal cam design.…”
Section: Introductionmentioning
confidence: 99%